Keep Calm in Heated Debates: How People Perceive Different Styles of Discourse in a Scientific Debate - Tkotz, Juliane; Kienhues, Dorothe; Jucks, Regina; Bromme, Rainer (Frontiers in Education, 2021)
Scientific debates are, in an epistemological sense, argumentative approaches aimed at coming to the most appropriate conclusion. However, as these debates sometimes involve interpersonal rather than content-driven attacks (e.g., an argument between scientific experts might involve personal dislike), the following question arises: How do such communication behaviors affect people’s perception of the argument? In an empirical study, we presented prospective teachers (N = 222) with a newspaper article about two scientific experts controversially discussing the pros and cons of a fictional vocabulary training program. Using a 1x2 between-subject design, the article contained either a neutral or an incivil discourse style. The dependent measures evaluated how participants perceived the experts’ trustworthiness and how they viewed the practical relevance of the scientific topic at hand. Results revealed that participants who read the neutral-style discourse perceived the two experts as having more expertise, higher integrity, and higher benevolence than participants who read the incivil-style discourse. However, the groups did not differ in their ratings of how beneficial the scientific findings might be in the classroom. Overall, this study shows that discourse style indeed influences the perceived trustworthiness of experts, in that it might be damaged in heated debates. The study therefore suggests that the scientific community’s methodological and social conventions should be addressed in higher education, in this case teacher education, as understanding these conventions is important for substantially evaluating heated scientific debates.